Exome sequencing of synchronously resected primary colorectal tumours and colorectal liver metastases to inform oncosurgical management. Issue 1 (January 2018) - Sutton, P.A.; Jithesh, P.V.; Jones, R.P.; Evans, J.P.; Vimalachandran, D.; Malik, H.Z.; Park, B.K.; Goldring, C.E.; Palmer, D.H.; Kitteringham, N.R.
Abstract: Background: Next generation sequencing technology has facilitated mapping of the colorectal cancer genotype and furthered our understanding of metastogenesis. The aim of this study was to investigate for conserved and different mutations in the exomes of synchronously resected primary colorectal tumour and liver metastases. This information could potentially be utilised to guide the treatment of advanced disease with the help of biological information from the primary tumour. Methods: We performed exome sequencing of synchronously resected primary colorectal cancer and colorectal liver metastases as well as normal colonic mucosa and liver parenchyma, from four patients who had received neo-adjuvant chemotherapy, at a depth of 50X using the Ion Proton platform. Raw data was mapped to the reference genome prior to variant calling, annotation and downstream analysis. Results: Exome sequencing identified 585 non-synonymous missense single nucleotide variants (SNVs), of which 215 (36.8%) were unique to the primary tumour, 226 (38.6%) unique to the metastasis and 81 (13.8%) present in patient matched pairs. SNVs identified in the ErbB pathway appear to be concordant between primary and metastatic tumours. Conclusion: Only 13.8% of the metastatic exome can be predicted by the genotype of the primary tumour. We have demonstrated concordance of a number of SNVs in the ErbB pathway, which may inform selection of therapeutic agents in advanced colorectal cancer.